An Usability Evaluation of the English Education Study Program Website Using the System Usability Scale - Wahyu Hidayat; David Naista; Ghifar Javad H Aziz (CHAIN: Journal of Computer Technology, Computer Engineering, and Informatics, 2026)
The English Education Study Program website serves as an essential platform for disseminating academic information, supporting communication, and providing various services to students, prospective students, alumni, and others. The effectiveness of a website depends not only on the availability of information but also on its usability, which determines how easily users can interact with and benefit from the system. This study aims to evaluate the usability of the English Education Study Program website https://english.tarbiyah.radenintan.ac.id using the System Usability Scale (SUS). A quantitative descriptive approach was employed, involving website users as respondents. Data were collected through a SUS questionnaire consisting of ten standardized statements measured using a five-point Likert scale. The collected responses were analyzed by calculating individual SUS scores and determining the overall usability score of the website. The evaluation focused on key usability aspects, including learnability, efficiency, effectiveness, consistency, and user satisfaction. The website obtained an average SUS score of 78.5 out of 100. Base on that, the findings identify strengths and areas that require improvement to enhance the user experience and optimize information services. The study demonstrates that the SUS method is a practical and reliable tool for measuring website usability and generating valuable feedback for website development. In addition, the study contributes empirical evidence by comparing the obtained SUS score with previous website usability studies. The conclusions can be used as a basis for improving the quality of the English Education Study Program website and ensuring that it better meets the needs and expectations of its users.